2016
DOI: 10.1039/c6nj01667g
|View full text |Cite
|
Sign up to set email alerts
|

3-Aminothiophenecarboxylic acid (3-Atc)-induced folding in peptides

Abstract: This article demonstrates the consequences of incorporating a constrained β-amino acid into a peptide chain and its effect on conformation of oligomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The small coefficients of HNA (−2.5 ppb/K) and H'NA (−2.6 ppb/K) indicate that neither one is intramolecularly H‐bonded. Additionally, solvent polarity titration (CDCl 3 /[D 6 ]DMSO) showed a little variance of HNiBu chemical shift (<0.22 ppm) with increasing fraction of [D 6 ]DMSO (Figure 2b), revealing its involvement in a strong intramolecular H‐bond, that resists solvation by competing polar solvent [29,30] . In contrast, the H'NiBu signal showed a sharp downfield shift, similar to the solvent‐exposed amide hydrogen (HN2 ) in the model compound A , which cannot form any intramolecular H‐bond.…”
Section: Figurementioning
confidence: 99%
“…The small coefficients of HNA (−2.5 ppb/K) and H'NA (−2.6 ppb/K) indicate that neither one is intramolecularly H‐bonded. Additionally, solvent polarity titration (CDCl 3 /[D 6 ]DMSO) showed a little variance of HNiBu chemical shift (<0.22 ppm) with increasing fraction of [D 6 ]DMSO (Figure 2b), revealing its involvement in a strong intramolecular H‐bond, that resists solvation by competing polar solvent [29,30] . In contrast, the H'NiBu signal showed a sharp downfield shift, similar to the solvent‐exposed amide hydrogen (HN2 ) in the model compound A , which cannot form any intramolecular H‐bond.…”
Section: Figurementioning
confidence: 99%
“…Earlier, we have reported that proline‐aminothiophene carboxylate dipeptide motifs (Pro‐Atc) n can generate conformationally constrained peptide structures (Figure ) . The presence of constrained aromatic β‐amino acid Atc was shown to assist in rigidifying the peptide backbone …”
Section: Figurementioning
confidence: 99%